Serum Elabela Level Significantly Increased in Patients with Complete Heart Block - Acele,Armağan (2020)
Abstract Objective: To investigate the change in serum Elabela level, a new apelinergic system peptide, in patients with complete atrioventricular (AV) block and healthy controls. Methods: The study included 50 patients with planned cardiac pacemaker (PM) implantation due to complete AV block and 50 healthy controls with similar age and gender. Elabela level was measured in addition to routine anamnesis, physical examination, and laboratory tests. Patients were divided into two groups, with and without AV block, and then compared. Results: In patients with AV block, serum Elabela level was significantly higher and heart rate and cardiac output were significantly lower than in healthy controls. Serum Elabela level was found to be positively correlated with high-sensitive C-reactive protein and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels, but negatively correlated with heart rate, high-density lipoprotein cholesterol, and cardiac output. In linear regression analysis, it was found that these parameters were only closely related to heart rate and NT-proBNP. Serum Elabela level was determined in the patients with AV block independently; an Elabela level > 9.5 ng/ml determined the risk of complete AV-block with 90.2% sensitivity and 88.0% specificity. Conclusion: In patients with complete AV block, the serum Elabela level increases significantly before the PM implantation procedure. According to the results of our study, it was concluded that serum Elabela level could be used in the early determination of patients with complete AV block.